Electrically tunable terahertz metamaterials based on graphene stacks array. (December 2017) - Liu, Hanqing; Liu, Peiguo; Bian, Li-an; Liu, Chenxi; Zhou, Qihui; Chen, Yuwei
Abstract: With the ability of tuning chemical potential via gate voltage, the permittivity of graphene stack can be dynamically adjusted over a wide range. In this paper, we design electrically tunable metamaterials based on the graphene/Al2 O3 stacks array, which can achieve a good modulation of resonant frequency and peak value in terahertz region. Due to the enlargement of plasmonic resonance response and the broaden distribution of electric field, our proposed structures perform a better tunability compared with traditional metamaterials loaded monolayer graphene. Since the dipole-dipole coupling between adjacent stacks strengthens immensely as reduces the filling factor of array, the modulated capacity could be further improved. It is found that for oblique incidence, the transmission property is also sensitive to the chemical potential of graphene as well as the polarization direction of incident terahertz wave. These results could be very instructive for the potential applications in voltage-sensitive devices, tunable sensors and photovoltaic switches. Highlights: The permittivity of unit graphene/Al2 O3 stack can be modulated apparently through bias voltage. Electrically tunable metamaterials is designed using a pair of graphene stack (GSMM) and graphene stacks array (GSAMM). Compared with monolayer graphene, the stacks array can enlarge the plasmonic resonance and then improve the tunability. Through reducing the filling factor of graphene stacks array, the tunability of GSAMM can be further enhanced. For the oblique incidence on GSAMM, a good switching characteristic is achieved by modulating the Fermi level of graphene.